Pelaksanaan Investasi dalam Pengembangan Kawasan Budidaya Pertanian di Kabupaten Buleleng - I Gusti Made Ngurah Bagus Andre Wedananta; I Nyoman Putu Budiartha; Putu Ayu Sriasih Wesna (Warmadewa Press, 2020)
One area carrying out development in Indonesia is Buleleng Sub-district in the Province of Bali. The development of the region is merely focused on developing the economic sector with priority on the agricultural sector expansion in a broad sense which is supported by the development of the tourism sector. One part of the agricultural sector development is the agricultural cultivation areas in the broadest sense with the support of funds from investment. Unfortunately, in reality, the development of this cultivation does not seem to have proceeded as expected. Therefore, this study addresses two issues related to this development. The first is whether or not the laws and regulations governing the development have been sufficiently capable of attracting the interest of investors in efforts to develop agricultural cultivation areas in the region of Buleleng, and the second is the extent to which the process of implementation of the development of agricultural area cultivation in Buleleng area has reached as well as obstacles encountered. To achieve these objectives, this study was conducted using the design and method of normative research and empirical legal research and also used statutory and conceptual approaches. The results of show the set of laws and regulations have the sufficient power to support the development of agricultural cultivation in the area, and the implementation of agricultural development in a broad sense has been carried out, and even the results have been felt and enjoyed by the community. One leading obstacle factor found is conversion of land functions along with evolution and revolution in human life. The attention and intervention of various parties in the efforts to develop and extend the areas in Buleleng Sub-district is still crucially necessary.